Lack of association of interferon regulatory factor 1 with severe malaria in affected child-parental trio studies across three African populations. - Valentina D Mangano; Taane G Clark; Sarah Auburn; Susana Campino; Mahamadou Diakite; Andrew E Fry; Angela Green; Anna Richardson; Muminatou Jallow; Fatou Sisay-Joof; Margaret Pinder; Michael J Griffiths; et al. (PLoS ONE)
Interferon Regulatory Factor 1 (IRF-1) is a member of the IRF family of transcription factors, which have key and diverse roles in the gene-regulatory networks of the immune system. IRF-1 has been described as a critical mediator of IFN-gamma signalling and as the major player in driving TH1 type responses. It is therefore likely to be crucial in both innate and adaptive responses against intracellular pathogens such as Plasmodium falciparum. Polymorphisms at the human IRF1 locus have been previously found to be associated with the ability to control P. falciparum infection in populations naturally exposed to malaria. In order to test whether genetic variation at the IRF1 locus also affects the risk of developing severe malaria, we performed a family-based test of association for 18 Single Nucleotide Polymorphisms (SNPs) across the gene in three African populations, using genotype data from 961 trios consisting of one affected child and his/her two parents (555 from The Gambia, 204 from Kenya and 202 from Malawi). No significant association with severe malaria or severe malaria subphenotypes (cerebral malaria and severe malaria anaemia) was observed for any of the SNPs/haplotypes tested in any of the study populations. Our results offer no evidence that the molecular pathways regulated by the transcription factor IRF-1 are involved in the immune-based pathogenesis of severe malaria.